2017
DOI: 10.1002/ejhf.799
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin inhibition in heart failure: mechanisms and substrates beyond modulating natriuretic peptides

Abstract: The autonomic nervous system, the renin-angiotensin-aldosterone system, and the natriuretic peptide system represent critical regulatory pathways in heart failure and as such have been the major targets of pharmacological development. The introduction and approval of angiotensin receptor neprilysin inhibitors (ARNi) have broadened the available drug treatments of patients with chronic heart failure with reduced ejection fraction. Neprilysin catalyses the degradation of a number of vasodilator peptides, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 77 publications
4
77
1
1
Order By: Relevance
“…Coherently with echocardiographic measurements, neprilysin inhibition mediated by sacubitril acutely amplified the hemodynamic effects of natriuretic peptides determining natriuresis and vasodilation [11,12] which resulted in decreased neurohormonal activation as our data have demonstrated by NT-proBNP concentrations abatement at follow-up.…”
Section: Discussionsupporting
confidence: 66%
“…Coherently with echocardiographic measurements, neprilysin inhibition mediated by sacubitril acutely amplified the hemodynamic effects of natriuretic peptides determining natriuresis and vasodilation [11,12] which resulted in decreased neurohormonal activation as our data have demonstrated by NT-proBNP concentrations abatement at follow-up.…”
Section: Discussionsupporting
confidence: 66%
“…A paradigm shift has occurred after the demonstration of its superiority over enalapril in patients with HFrEF . Neprilysin inhibition causes an increase of many different peptides, including atrial, brain, C‐type natriuretic peptides (ANP, BNP, CNP), bradykinin, substance P, adrenomedullin, whose effects on the cardiovascular system and their role as biomarkers are nicely summarized in this issue of our journal …”
Section: Biomarkersmentioning
confidence: 99%
“…D'Elia et al review the neurohormonal changes induced by the administration of an angiotensin receptor‐neprilysin inhibitor (ARNI), sacubitril/valsartan . A paradigm shift has occurred after the demonstration of its superiority over enalapril in patients with HFrEF .…”
Section: Biomarkersmentioning
confidence: 99%
“…The PARADIGM-HF study showed that the number of confirmed angioedema cases for sacubitril/ /valsartan as compared to enalapril during a double-blind trial was 19 (0.45%) vs 10 (0.24%) (the relative risk was 1.9 [95%CI 0.8-4.5], thus the risk of occurrence of this adverse reaction was assessed as low. It is worth mentioning that no increased risk of angioedema was observed in current smokers administered sacubitril/valsartan or enalapril [8].…”
mentioning
confidence: 89%